Tool coating effects on cutting temperature during metal cutting processes: Comprehensive review and future research directions. (March 2021) - Zhao, Jinfu; Liu, Zhanqiang; Wang, Bing; Hu, Jianrui; Wan, Yi
Highlights: Tool coating effects on cutting temperature in metal cutting process are reviewed. Factors influencing on cutting temperature with coated tools are analyzed. Measurements and determination approaches of the influencing factors are illustrated. Predictive modelling methods for cutting temperature with coated tool are discussed. Measurement technologies on cutting temperature with coated tool are illustrated. Abstract: Nowadays, coatings have been widely deposited on cutting tool inserts due to their superior wear resistant and thermal barrier effect in metal manufacturing industry. Tool coatings avoid the direct contact between the workpiece and tool substrate, thus affecting the cutting temperature and machining performance compared with uncoated tools. This article aims to review the tool coating effects on cutting temperature during metal cutting process. Firstly, the factors influencing on cutting temperature with coated tools are analyzed including the geometric factors, thermal physical properties, coated tool-chip contact characteristics and coating-substrate diffusion layer. The determination approaches of these influencing factors are illustrated. Secondly, the predictive modelling for cutting temperature with coated tool including analytical thermal models and simulation methods (finite element method-FEM, finite difference method-FDM, boundary element method-BEM) are discussed, respectively. Thirdly, the experimental measurements on cutting temperature with coated tool are reviewed and analyzed. The possible perspectives of future work for investigating the tool coating effects on cutting temperature are proposed. This review would help to obtain knowledge of tool coating effects on cutting temperature with coated tools, thus for better selection and design suitable tool coatings by decreasing cutting temperature.